EMPHYSEMATOUS PYELONEPHRITIS: A CASE REPORT - NS, Neki; Joshi, Neeraj; Singh Shergill, Gagandeep; Singh Dhanju, Amandeep (International Journal of Clinical and Biomedical Research, 2017)
Emphysematous pyelonephritis is a rare life threatening fulminant necrotizing infection of the kidney with high mortality. It is characterized by characteristic gas formation within or around the kidney on radiological investigations, while E.Coli is the most common causative organism. We report a case of 60 year old female suffering from diabetes mellitus since 3 years, who presented with high grade fever, abdominal pain, vomiting and dysuria. She was diagnosed as a case of emphysematous pyelonephritis and successfully treated. KEYWORDS: Emphysematous pyelonephritis; Antibiotics.